Kant and Jewish philosophy - Sheʾar-Yashuv, Aharon 1940- (1995)
The main purpose of the article is to explain why most modern Jewish philosophers belong to the Kantian school. This is obviously surprising since Kant — though he had friendly relationships with Jewish thinkers like Moses Mendelssohn, Solomon Maimon, and with his Jewish students, like Marcus Herz, nevertheless criticized Judaism as not being a religion but only a nation being based on law which is of non-ethical character. We show that inspite of his obviously critical view of Judaism, Kant nevertheless was influenced by Jewish, especially Maimonidean thoughts. This might be the reason for his strong impact on Jewish Liberal and Orthodox thinkers, like Salomon Ludwig Steinheim, Hermann Cohen, Isaac Breuer, and others. This does not justify the term "Jewish Kantian," because all these Jewish philosophers and theologians only try to express their Judaism with the tools of Kantian philosophy which is judged by them — every one from his specific point of view — critically, according to their understanding of Jewish tradition.
Keywords: Kant, Immanuel -- 1724-1804